Interdisciplinary economics : Kenneth E. Boulding's engagement in the sciences - Boulding, Kenneth E. (Kenneth Ewart), 1910-1993 (Routledge studies in the history of economics ;, 2013)
Kenneth Boulding was a prolific writer across so many different fields that not only is he often much referred to and cited, he is considered a core member of many of these fields. Boulding is the quintessential interdisciplinary scholar. He died in 1993, but he has left a legacy in economics, conflict studies, systems theory, ecology, biology, communication studies, and ethics. As an economist proper he has tested and expanded the boundaries of that field without unduly ""invading"" and undermining the expertise and established knowledge of the other social sciences. This proposed volume w.